Slope of Spectral Amplitude: Simple Yet Effective Hydrocarbon Indicator - Gadang Gentur Wihardy; Hilfan Khairy (Jurnal Geofisika, 2021)
Spectral decomposition has been developed and used for many years to help understanding the subsurface condition. Numerous different approach and specific application of this methodology have been proposed and each of the approach has its own advantages. Slope of Spectral Amplitude is a new spectral decomposition based methodology, which is developed based on the intrinsic seismic attenuation phenomenon affecting the seismic spectrum. The difference of spectrum will be characterized by Intercept and Gradient parameters. These parameters can be used to identify the presence of hydrocarbon from seismic data. Further extension of this concept, transformed the Intercept and Gradient result into Gas Probability data which indicates high probable gas occurrence. Good relationship between gas occurrences confirmed by wells with the resulted Intercept, Gradient and Gas Probability data is shown through several examples presented in this study. These examples cover different seismic data environment and different interval of analysis.